Analisis Efektifitas Instalasi Pengolahan Limbah Lindi Di TPA Supit Urang Kota Malang - Saleh, Chairil; Purnomo, Hendro (Fakultas Teknik, Universitas Brawijaya, 2014)
Leachate is the liquid waste as consequence of water which flow into the influx of external water into the embankment of waste / garbage and then rinsed and dissolved the material in the embankment, so it has a variety of organic and inorganic pollutants.Leachate sewage treatment instalation is a the installation that processed waste leachate in order not to contaminate the environment of the river. The negative impact of leachate is to killed an existing biota in of the river, groundwater contamination, especially in the areas where rainfall and high soil water level. This study was conducted at the landfill Supit Urang in the Village Mulyorejo with 19.6 hectares. Waste disposed to Supit Urang landfill approximately Â± 400 tons / day, and area of 75% of the total area has been filled with garbage. It has the potential to generate leachate wastewater. Therefore, it is required the leachate treatment waste installation that is storage ponds, consisting of stabilization ponds, aeration ponds and pools maturisasi waste leachate. The objective of this study was to determine the effectiveness of waste leachate treatment facility.The capacity of the reservoir pondswas determined by the discharge of leachate and leachate production. Effectiveness of the sewage treatment plant was determined by reduction in the quality of leachate as decreased content of COD and BOD from the waste dumped in landfill Supit Urang.Result showed that there wasthe leachate discharge obtained 9.43 m3/day and leachate production was 0.8 m3/day. Before entering the waste leachate, the content of COD = 8960 mg / l and BOD 5 = 3968.293 mg / l of leachate treatment plant. Before sewage treatment plants, the content of COD = 298.67 mg / l and BOD = 88.18 mg / l. Thus the effectiveness of the leachate treatment plant, COD and BOD can reduce 97%..From the processing of waste leachate treatment plant already appropriate with the water quality standards according to Keputusan Menteri No. 03 /1991 which includes group III.Keywords: Leachate, leachate treatment sewage instalation, COD and BOD 5